Prospect research for fundraisers : the essential handbook - Filla, Jennifer J., 1970-; Brown, Helen E., 1963- (Hoboken, New Jersey : John Wiley & Sons, Inc., 2013)
Essential tools for implementing right-sized prospect research techniques that help nonprofit organizations reach their fundraising goals Written especially for front-line fundraisers, Prospect Research for Fundraisers presents a practical understanding of prospect research, prospect management, and fundraising analytics, demonstrating how research can be used to raise more money. Filled with examples, case studies, interviews, and stories, this unique book is structured around the fundraising cycle and illustrates the myriad of current and ever-changing prospect research tools.
Includes index.
Print version record and CIP data provided by publisher.
Keywords: Fund raising; Fund raisers (Persons); BUSINESS & ECONOMICS -- Investments & Securities -- General; Fund raisers (Persons); Fund raising; Electronic books